Cost-Effectiveness Analysis of Nivolumab Plus Ipilimumab for Advanced Non-Small-Cell Lung Cancer - Xiaomin Wan; Xiaohui Zeng; Liubao Peng; Ye Peng; Qiao Liu; Lidan Yi; Xia Luo; Qijian Deng; Qijian Deng; Chongqing Tan (Frontiers Media S.A., 2021)
Objective: This study evaluated the cost-effectiveness of nivolumab plus ipilimumab vs. chemotherapy in the first-line setting for patients with advanced non-small-cell lung cancer (NSCLC) from the US payer perspective.Materials and methods: A Markov model wasdeveloped to evaluate the cost and effectiveness of nivolumab plus ipilimumab vs. chemotherapy in the first-line treatment of advanced NSCLC. The survival benefits of nivolumab plus ipilimumab were based on the results of the CheckMate 227 trial. The main endpoints of the model were cost, life-years (LYs), quality-adjusted LYs (QALYs), and incremental cost-effectiveness ratio (ICER). Univariable and probabilistic sensitivity analyses were conducted to assess model uncertainty. Additonal subgroup analyses were also performed.Results: nivolumab plus ipilimumab produced a gain of 0.62 QALYs, at a cost of $104238 per QALY. The variables that had the greatest influence on the ICER were body weight and overall survival (OS) hazard ratio (HR). The probability of nivolumab plus ipilimumab being cost-effectiveness compared to chemotherapy is 50.7 and 66.2% when the willingness-to-pay (WTP) value is $ 100,000 and $ 150,000 per QALY. The results of subgroup analyses showed the ICER remained below $150,000/QALY regardless of the PD-L1 expression level.Conclusions: nivolumab plus ipilimumab was estimated to be cost-effective compared with chemotherapy for patients with advanced NSCLC at a WTP threshold from 100,000/QALY to 150,000/QALY.